STUDIES OF THE BHK-21/2-17 LINEAGE USING FLOW CYTOMETRY - M. A. Shevchenko; M. N. Guseva; D. V. Mikhalishin; B. L. Manin; A. A. Shishkova (Ветеринария сегодня)
The paper presents results of the ВНК-21/2-17 lineage cell cycle tests using flow cytometry. This cell line is widely used in biological industry that is why studying the ВНК-21/2-17 cell suspension pattern using the proposed technique and determination of tools and methods to prevent morphological and structural cell modifications in the culture affected by negative factors is of great interest. Flow cytometry allows to determine quantitative parameters of cell cycle phases and perform correlation between these phases and viability of the working cell population. It was mentioned that the general trend of this cell lineage suspension cultivation for 48 hours has a standard dynamics, herewith at all stages of the cell cycle the primary growth stage - G1 prevailed. Under unfavorable conditions of cultivation apoptotic debris could increase up to 31-59%, i. e. part of the cell population could be potentially non-reproductive. Unsuccessful cultivation stages associated with low pH content in the cultivator where pH was not maintained at the constant level were detected. During optimization of cell cultivation physical and chemical parameters proliferation intensity increased. Viable cell yield during cultivation when a specific pH was maintained was higher and at the synthetic stage G2 + M no cycle delay occurred.